Role of Cagayan community schools in the development of the swine industry in Cagayan - Acorda, Sabino 1910- (s.n.], 1962)
This study investigates how education promotes community improvement. This has been undertaken to present comprehensive information and data concerning the practices and status of the swine industry in Cagayan and how the schools helped in the development of this industry. It purports to furnish proper answers on how Cagayan community schools have utilized education to expand the swine industry in Cagayan.